Role of Conventional Cytogenetics and FISH in the Laboratory Work Up of Plasma Cell Dyscrasias - Dhabe, Aaishwarya; Das, Samipa; Parihar, Mayur (Indian Journal of Medical and Paediatric Oncology, 2023)
Plasma cell dyscrasias are a heterogeneous group of neoplasms characterized by abnormal proliferation of plasma cells with or without over production of monoclonal immunoglobulins. Chromosomal abnormalities are acquired either early in the course of the disease or during disease progression. Plasma cell dyscrasias are categorized into multiple cytogenetic subtypes that form an integral component of risk-stratified treatment protocols. The primary genetic events are IgH gene translocations and non-random gains of chromosomes 3/5/7/9/11/15/19 and or 21. The secondary genetic events consist of chromosome 1 abnormalities (1p deletion and 1q gain or amplification), deletion 17p/TP53, deletion 13q, and MYC gene rearrangements. Plasma cells being at the end of differentiation spectrum of B cells, have low proliferative potential precluding the use of karyotyping in identification of chromosomal abnormalities. Analysis of enriched plasma cells using interphase fluorescent in situ hybridization (FISH) is the technique of choice for identifying these abnormalities. It is essential to enrich plasma cells before the FISH analysis, and numerous plasma cell enrichment techniques have been described. In the paper, we review the cytogenetic approach to identify clinically significant genetic aberrations including the effective use of FISH panels and plasma cell enrichment techniques.
Keywords: plasma cell dyscrasia; multiple myeloma; FISH; MGUS; SMM; plasma cell leukemia; cytogenetics in myeloma